If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 + k = 26 Solving 23 + k = 26 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-23' to each side of the equation. 23 + -23 + k = 26 + -23 Combine like terms: 23 + -23 = 0 0 + k = 26 + -23 k = 26 + -23 Combine like terms: 26 + -23 = 3 k = 3 Simplifying k = 3
| 70=3x+10 | | 2y-8=-14+5y | | K-8=7 | | 2d-8=5d-4 | | -13/17-8(48y-97)=x | | 4.35(19)+3.42f=82.35 | | Y=8(0.25)x | | 3x+11=8-2x | | 2x+4y=268 | | 5y+2-5y=2 | | 9n^2+6=7n | | r^2=8r-7 | | 4y-2y+16=8y+20-5y | | 4.35b+3.42f=82.35 | | -5(-x-3)=-60 | | 2.6(j-1)+0.7=1.2(3-j)+0.2 | | 5x-(5)-10=0 | | 5(-6n+12)-35(4n-22)=-20 | | F(x)=(7x+10)3 | | 2x+11+3x-9=180 | | 3(3s+9)=54 | | 75y^3=200y^2+27y-72 | | 4(4-x)=4 | | -3+(2+4x)= | | k^2-121=0 | | 6g+3(-4+3g)=1-g | | t^2-145t+2500=0 | | -10a^2+2a-4=-12a^2 | | 6y+7x=36 | | 9x+8=15y | | 7(2l+8)=154 | | c^2-11c+24= |